Assessing the progress of Mycobacterium tuberculosis H37Rv structural genomics. Issue 2 (March 2015) - Fang, Zhuo; van der Merwe, Ruben Gerhard; Warren, Robin Mark; Schubert, Wolf-Dieter; Gey van Pittius, Nicolaas Claudius
Summary Tuberculosis threatens human health nowhere more than in developing countries with large malnourished and/or immune-compromised (e.g. HIV infected) populations. The etiological agent, Mycobacterium tuberculosis (Mtb), is highly infectious and current interventions demonstrate limited ability to control the epidemic in particular of drug resistant Mtb strains. New drugs and vaccines are thus urgently required. Structural biologists are critical to the TB research community. By identifying potential drug targets and solving their three dimensional structures they open new avenues of identifying potential inhibitors complementing the screening of novel compounds and the investigation of Mtb's molecular physiology by pharmaceutical companies and academic researchers. Much effort has gone into structurally elucidating the Mtb proteome though much remains to be done with progress primarily limited by technological constraints. We review the currently available data for Mtb H37Rv to extract the lessons they have taught us.